2018
DOI: 10.1002/hpm.2639
|View full text |Cite
|
Sign up to set email alerts
|

What is the supporting role of health care providers from the perspective of patients with renal allograft rejection? A qualitative study

Abstract: Coping with the new conditions for patients with renal allograft rejection is a complex phenomenon influenced by a number of factors. It appears that the supportive role of health care providers in many aspects is 1 of the most important factors in patient satisfaction, increased quality of life, and application of proper coping mechanisms. This study explored the perceptions of patients with renal allograft rejection about the supportive role of health care providers. This study was conducted with a qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Those who knew about their medications were in a better position to ask questions and were able to solve problems and discuss strategies to cope with side effects 24,29,36‐38,49,77,109 . They became more confident in their medication regime through better knowledge and understanding 21,22,24,25,45,53‐55,58,73,84,86,87,93,96,97,108,110‐113 . They trusted and valued clinicians as a key source of information and were adherent to medication adjustments (e.g., changing medications, dosing) to minimize side effects 21,22,25,29,35,44,46,50,51,57,58,66,68,71,77,79,82,87,95,98,99,103,108,110,114‐116 …”
Section: Resultsmentioning
confidence: 99%
“…Those who knew about their medications were in a better position to ask questions and were able to solve problems and discuss strategies to cope with side effects 24,29,36‐38,49,77,109 . They became more confident in their medication regime through better knowledge and understanding 21,22,24,25,45,53‐55,58,73,84,86,87,93,96,97,108,110‐113 . They trusted and valued clinicians as a key source of information and were adherent to medication adjustments (e.g., changing medications, dosing) to minimize side effects 21,22,25,29,35,44,46,50,51,57,58,66,68,71,77,79,82,87,95,98,99,103,108,110,114‐116 …”
Section: Resultsmentioning
confidence: 99%
“…Nurses should strengthen their resilience and develop resilience skills to deal with difficulties, adapt to new conditions, have realistic and positive expectations, and protect work and life. Studies have shown that nurses with high resilience are less prone to stress disorders and more likely to remain healthy (Ebadzadeh et al., 2019; Mahdavifar et al, 2020; Turner, 2014). This concept is very important for nurse managers because resilience may play an important role in nurses' longevity and protection against crises, including the COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the type of hospital and working environment play an essential role in nursing care, perception of holistic care and satisfaction of patients. In confirming this issue, a number of studies reported that many factors such as working environment, in-service training, management quality and timeliness affects the quality of nursing care and patients’ satisfaction [30, 31].…”
Section: Discussionmentioning
confidence: 99%